A PHILOSOPHICAL ANALYSIS OF THE CONCEPTS OF RESPECT AND COOPERATION IN NIGERIA'S CIVIC EDUCATION CURRICULUM (2013)
Respect and cooperation are concepts of social values that accord dignity, honour to others and ensure collaboration to achieve a common goal. They are very important in the intellectual and moral development of learners and in the social transformation of learners for the development of the society. Many researches in philosophy of education have focussed more on the cognitive and psychomotor domains of learning than on the affective domain. However, one can see value decadence as exhibited by graduates of our schools. This study, therefore, examined the concepts of respect and cooperation and their place in the philosophy of education, the Kantian categorical imperatives, as well as Mill and Bentham's philosophy of utilitarianism. It also explained the relevance of the nation's academic curriculum in Civic education to the attainment of national goals through the values of respect and cooperation. This is with a view to identifying the Civic education curriculum as a possible avenue for developing the values of respect and cooperation which constitutes part of our national goals of education. The Civic education curriculum by the Federal Ministry of Education for the basic education and senior secondary schools 2009 and 2011 respectively were examined in this study with focus on the attitude development components. The study employed the speculative, normative and analytic philosophical methods conjointly to analyse the target concepts and establish the ideals as well as relationship between thought and experience about the world. The methods were also adopted to prescribe how to inculcate and acquire knowledge of social values in the society. Social values are qualities, principles and attributes that make human behaviour acceptable socially and are very significant in ethics and education. These values include respect and cooperation. They are cognitive and affective and are pertinent for individual and social development as contained in the Civic education curriculum. These values encourage positive social relationships as exemplified in Kant's imperatives as well as Mill's and Bentham's utilitarianism. In Kant's imperatives, respect enables individuals to treat others as ends not as means of attaining ends, while this value in utilitarianism stipulates that we ensure maximum benefits for the greatest number of people. Cooperation on the other hand inspires team work in Kant's imperatives while it produces greatest benefits for the people through collaboration in utilitarian ethics. A curriculum model that would incorporate both cognitive and affective development of the values of respect and cooperation was developed and illustrated.